Prospect of Increased Disruption to the QBO in a Changing Climate. Issue 15 (5th August 2021) - Anstey, James A.; Banyard, Timothy P.; Butchart, Neal; Coy, Lawrence; Newman, Paul A.; Osprey, Scott; Wright, Corwin J.
Abstract: The quasi‐biennial oscillation (QBO) of tropical stratospheric winds was disrupted during the 2019/20 Northern Hemisphere winter. We show that this latest disruption to the regular QBO cycling was similar in many respects to that seen in 2016, but initiated by horizontal momentum transport from the Southern Hemisphere. The predictable signal associated with the QBO's quasi‐regular phase progression is lost during disruptions and the oscillation reemerges after a few months significantly shifted in phase from what would be expected if it had progressed uninterrupted. We infer from an increased wave‐momentum flux into equatorial latitudes seen in climate model projections that disruptions to the QBO are likely to become more common in future. Consequently, it is possible that in the future, the QBO could be a less reliable source of predictability on lead times extending out to several years than it currently is. Plain Language Summary: The quasi‐biennial oscillation (QBO) consists of a regular switching between eastward and westward winds in the tropical stratosphere. The oscillation has persisted at least since its discovery in the 1960s, over which time its period averages about 28 months with some variability from cycle to cycle. Recently, during the Northern Hemisphere winters of 2015/16 and 2019/20, remarkable departures from this regular behavior occurred that have no precedent in the observational record. Both the 2015/16 and 2019/20 QBO disruptions occurred when large horizontal fluxes of momentum intruded into the tropics from higher latitudes. Using climate model projections, we find these horizontal fluxes are likely to increase in future, suggesting an increased future likelihood of QBO disruptions and a concomitant loss in QBO predictability. Key Points: A second recent disruption of the quasi‐biennial oscillation (QBO) has occurred Large momentum fluxes from the Southern Hemisphere made a substantial contribution to the 2019/20 disruption Increased equatorward momentum flux in climate model projections suggests QBO disruptions may become more likely in future